The Effect of Financial Performance and Good Corporate Governance on Share Prices in Sharia Commercial Banks Listed on the Indonesia Stock Exchange - Nasution, Qisti Marhamah; Hayono, Slamet (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2023)
This study aims to ensure the effect of financial performance and good corporate governance on stock prices at Islamic commercial banks listed on the Indonesia Stock Exchange in 2018-2022. This approach is quantitative using secondary data in the form of panel data of 60 samples with data processing used through the Eviews 10 program. Financial performance variables are proxied by ROA and ROE. Good Corporate Governance is proxied by BOD and AC. The results showed that partially ROA and AC had a significant positive effect on stock prices. While ROE and BOD have no significant effect on stock prices. Simultaneously, ROA, ROE, BOD, and AC have a significant effect on stock prices by 71% and the remaining 29% is explained by other variables not included in this study.